Astrocytes in the Pathogenesis of Multiple Sclerosis: An In Situ MicroRNA Study. Issue 12 (23rd September 2019) - Rao, Vijayaraghava T S; Fuh, Shih-Chieh; Karamchandani, Jason R; Woulfe, John M J; Munoz, David G; Ellezam, Benjamin; Blain, Manon; Ho, Ming-Kai; Bedell, Barry J; Antel, Jack P; Ludwin, Samuel K
Abstract: Astrocytes are increasingly recognized as active contributors to the disease process in multiple sclerosis (MS), rather than being merely reactive. We investigated the expression of a selected microRNA (miRNA) panel that could contribute both to the injury and to the recovery phases of the disease. Individual astrocytes were laser microdissected from brain sections. We then compared the miRNAs' expressions in MS and control brain samples at different lesional stages in white versus grey matter regions. In active MS lesions, we found upregulation of ischemia-related miRNAs in white but not grey matter, often with reversion to the normal state in inactive lesions. In contrast to our previous findings on MS macrophages, expression of 2 classical inflammatory-related miRNAs, miRNA-155 and miRNA-146a, was reduced in astrocytes from active and chronic active MS lesions in white and grey matter, suggesting a lesser direct pathogenetic role for these miRNAs in astrocytes. miRNAs within the categories regulating aquaporin4 (-100, -145, -320) and glutamate transport/apoptosis/neuroprotection (-124a, -181a, and -29a) showed some contrasting responses. The regional and lesion-stage differences of expression of these miRNAs indicate the remarkable ability of astrocytes to show a wide range of selective responses in the face of differing insults and phases of resolution.